To prove the equivalence \( 12a + 10 + a = 10 + a + 12a \) using the Commutative Property, we need to rearrange the terms in the expression.
The correct missing step would be:
Step 1: \( 12a + 10 + a = 10 + a + 12a \)
Now let's rearrange the terms:
Step 2: \( 10 + 12a + a = 10 + a + 12a \) (using the Commutative Property).
This means that the correct missing step to complete the proof would be:
12a + 10 + a = 10 + 12a + a
However, looking at the provided options, the one that directly correlates with this logic is:
10 + 12a + a = 10 + 13a
So, writing that format eventually summarizes that:
10 + 12a + a = 10 + 13a.
Thus, the answer is: 10 + 12a + a = 10 + 13a.
If your choices need to match exactly to one from your list, it seems the best fit would be:
12a + 10 = 10 + 12a
This represents a symmetry, leading towards the same side of the equation equivalently showing the process of reaching an equivalent fact through switching the placement of the components in the equation.